2011
DOI: 10.1007/s13524-011-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Cohabitation History, Marriage, and Wealth Accumulation

Abstract: This study extends research on the relationship between wealth accumulation and union experiences, such as marriage and cohabitation. Using data from the National Longitudinal Survey of Youth 1979, we explore the wealth trajectories of married individuals in light of their premarital cohabitation histories. Over time, marriage positively correlates with wealth accumulation. Most married persons with a premarital cohabitation history have wealth trajectories that are indistinguishable from those without cohabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 57 publications
2
58
0
2
Order By: Relevance
“…At any given time point, marriage was strongly associated with neighborhood characteristics. Marriage was associated with lower neighborhood poverty, consistent with resource consolidation and stability that occur with marriage (Vespa and Painter 2011). We also found that marriage was associated with lower neighborhood density.…”
Section: Discussionmentioning
confidence: 70%
“…At any given time point, marriage was strongly associated with neighborhood characteristics. Marriage was associated with lower neighborhood poverty, consistent with resource consolidation and stability that occur with marriage (Vespa and Painter 2011). We also found that marriage was associated with lower neighborhood density.…”
Section: Discussionmentioning
confidence: 70%
“…We discovered that the trend for the association between marriage and screening was stable over time, and that the gap between married and unmarried did not grow over time. Despite social and economic changes over that period such as economic fluctuations and changing gender roles [1012], marriage appears to be a social status that consistently confers health-promoting behavioral advantages, which may partly explain why previous literature has consistently found that married persons have better health than unmarried persons [13]. Future research using data with a longer study period may be better able to capture variations in this association; perhaps the trend between marriage and screening was larger in prior generations and shrank over time, or perhaps in the coming years the gap will shrink.…”
Section: Discussionmentioning
confidence: 99%
“…Another view argues that marriage confers specific benefits for individuals such as social support, pooled assets, access to spousal health insurance, and shared household labor [5–9]. However, there is some evidence to suggest that the relationship between marriage and health changes over time concurrent with changes in social norms about marriage, gender roles, or economic climate [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…Debt, however, is distinct from income or wealth in that it must be repaid (Schneider, 2011; Vespa, 2011). Taking on debt for consumption, even consumption seen as a rational investment, thus puts future consumption at risk.…”
Section: Debt and Early Fertilitymentioning
confidence: 99%